Influence of biomass raw material on combustion durations of highly densified single cylindrical biomass briquette ( Research using artificially prepared biomass raw materials ) - Hiroyuki ITO; Masayoshi MIURA; Ryuichi ENDO; Ryo IWASAKI (Nihon Kikai Gakkai ronbunshu, 2023)
It is known that flaming combustion duration of highly densified single cylindrical biomass briquette is proportional to the product of the inverse square of the specific surface area and briquette density. It was suggested that the proportional constant Cf can be correlated with the mass percentage of holocellulose in the biomass. On the other hand, the char combustion duration is almost proportional to the product of the inverse square of the specific surface area and the fixed carbon content of the briquette. It was suggested that the proportional constant Cc can be correlated with the mass percentage of the ash content in the biomass. However, the individual influences of cellulose, hemicellulose and ash content on the flaming and char combustion durations, and thus on Cf and Cc, have not been clarified yet. In the present study, to investigate the effects of holocellulose content, ash content in raw materials, and cellulose (hemicellulose) content in holocellulose on Cf and Cc in detail, briquettes made of artificial raw materials adding cellulose, hemicellulose powder, cypress ash or rice husk ash to cypress or rice husk were burned in the hot air flow. It was confirmed that Cf increases with increasing the holocellulose content, however, there is less effect of the cellulose content in holocellulose, in the scope of this study. And it was suggested that low boiling component in briquette affects the Cf value. It was confirmed that increasing the ash content decreases 1/Cc, and the dependence decreases as the ash content increased. And it was confirmed that there is less effect of the holocellulose content, the cellulose content in holocellulose, ash type and low boiling point component on 1/Cc value.